Pendampingan Pembuatan NIB dan Pembukuan Sederhana Berbasis Digital pada UMKM Es Buah RL - Habib Naufal Firdaus; Diana Airawaty (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
The support for MSMEs (Micro, Small, and Medium Enterprises) is carried out through two different activities focused on business legality and the introduction of simple bookkeeping. First, a mentoring program for the use of the Buku Warung app helps MSMEs manage financial reports flexibly and efficiently. Through this training, MSMEs can record finances via a mobile app instead of manually, allowing for more consistent and streamlined record-keeping. Second, a mentoring program for obtaining a Business Identification Number (NIB) guides MSMEs in understanding the importance of NIB and the process to acquire it, which can open up access to funding and boost their economic growth. These two programs aim to strengthen MSMEs’ capacity in operational efficiency and business legality.